2015
DOI: 10.1016/j.rbmo.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of food intake and social habits on embryo quality and the likelihood of blastocyst formation

Abstract: The aim of this study was to evaluate the influence of patients' lifestyle factors and eating habits on embryo development. A total of 2659 embryos recovered from 269 patients undergoing intracytoplasmic sperm injection cycles were included. The frequency of intake of food items and social habits were registered and its influences on embryo development evaluated. The consumption of cereals, vegetables and fruits positively influenced the embryo quality at the cleavage stage. The quality of the embryo at the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 77 publications
5
51
0
1
Order By: Relevance
“…These findings were confirmed by a cross-sectional study investigating the impact of lifestyle interventions, due to upcoming infertility treatment, in women enrolled in ART; the results of the study demonstrated that women who abstained from drinking or reduced alcohol intake had increased odds of becoming pregnant, compared to women who maintained their habitual alcohol consumption prior to ART [140]. Additionally, a dosedependent negative effect of alcohol consumption on embryo quality [141,142], and reduced odds for blastocyst formation [142] were also detected. The discrepancy between findings on the impact of alcohol consumption on natural fertility and assisted reproduction are harsh to address, due to highly heterogeneous study designs, proxy reporting of exposure, and non-standardized assessment and quantification of exposure to alcohol, limitations affecting both types of studies; moreover, misalignment of results may be generated by the existence of extremely scarce investigations in the ART category, probably due to the high motivation in achieving a pregnancy in women enrolled in ART programs, which likely reduced the number of women reporting alcohol consumption prior to ART.…”
Section: Female Fertilitymentioning
confidence: 73%
“…These findings were confirmed by a cross-sectional study investigating the impact of lifestyle interventions, due to upcoming infertility treatment, in women enrolled in ART; the results of the study demonstrated that women who abstained from drinking or reduced alcohol intake had increased odds of becoming pregnant, compared to women who maintained their habitual alcohol consumption prior to ART [140]. Additionally, a dosedependent negative effect of alcohol consumption on embryo quality [141,142], and reduced odds for blastocyst formation [142] were also detected. The discrepancy between findings on the impact of alcohol consumption on natural fertility and assisted reproduction are harsh to address, due to highly heterogeneous study designs, proxy reporting of exposure, and non-standardized assessment and quantification of exposure to alcohol, limitations affecting both types of studies; moreover, misalignment of results may be generated by the existence of extremely scarce investigations in the ART category, probably due to the high motivation in achieving a pregnancy in women enrolled in ART programs, which likely reduced the number of women reporting alcohol consumption prior to ART.…”
Section: Female Fertilitymentioning
confidence: 73%
“…The extracted dietary pattern was also related to a very low intake of meat. Recent evidence has shown that highly processed meat intake is negatively associated with fertilization, implantation and pregnancy rates among couples undergoing conventional IVF. Moreover, a dietary pattern high in red meat has been negatively associated with second‐ and third‐trimester fetal growth parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, blastocyst formation following ART was decreased among patients consuming more red meat. However, blastocyst formation was positively affected by fish consumption (129).…”
Section: Proteinmentioning
confidence: 95%